FAKTOR PENYEBAB PERCERAIAN PADA PERNIKAHAN DINI PERIODE TAHUN 2020-2021 STUDI KASUS DI DESA KWADUNGAN KABUPATEN KEDIRI - Sinta Dewi Nur Aviva; Khoirul Asfiyak; Moh. Muslim (Jurnal Hikmatina, 2022)
Based on initial observations, it was found that many people are divorced but do not understand what are the factors that cause divorce and what the impact of divorce, especially on divorce actors in early marriage, is due to lack of socialization and limited public knowledge to seek related information for this.From the background of the research above, the formulation of the problem in this study is what are the factors that influence divorce in early marriage, how is the impact of post-divorce on early marriage.The purpose of this study was to determine the factors that influence divorce in early marriage and to find out how the impact of post-divorce on early marriage.This type of research is a case study with a descriptive approach. Data collection techniques were carried out through passive observation, then with semi-structured interviews, interviews were conducted in depth, and in practice it was more flexible where informants were asked for opinions, or ideas in it, as well as documentation.The results of this study indicate that there are several factors that cause divorce in early marriage, namely economic factors, age/age factors, communication factors, domestic violence factors, and moral factors. While the impact of divorce includes child development, trauma, psychology, reduced self-esteem, and property.Kata kunci: Factors Causing Divorce, Impact of Divorce